Eumaeine butterflies (Lepidoptera: Lycaenidae) from San Antonio hill: Dynamics of species richness and hilltopping behaviour - PRIETO, CARLOS; DAHNERS, HANS W. (Revista Colombiana de Entomología, 2006)
Richness of the tribe Eumaeini was analyzed on a temporal scale on San Antonio hill, west of Cali, based on collections made in 2003. Specimens were collected with 5 m and 1.8 m long insect nets in 92 surveys. Species accumulation curves and similarity analysis (Jaccard) were carried out to compare 11 months of the year with BiodiversityPro software and rarefaction curves made with Ecosim700. The richness of Eumaeini recorded on the hill reached 72 species distributed in 32 genera. Estimators indicated that about 88% of the species that fly in the zone were collected. At least 20 species were distributed across the entire year, have constant populations in San Antonio, and use the hill as a site for mate finding. At least 26 species were assumed to not display hilltopping behaviour or their populations were relatively low in the area around the hill.  The months of July and August showed a high number of species although the rarefaction analysis indicated that there was no significant differences in richness among the 11 months in 2003. The similarity between the months was less than 56% according to the Jaccard similarity analysis. The changes in community richness were principally due to the rain regime and to the greater or lesser influence of sun in the zone.  The great number of unique species could be due to individuals that do not display hilltopping behaviour or to those that come from distant sites that have large and stable populations.